(untitled) (Fiep Bulletin - online, 2014)
Stretching causes both acute and chronic effects on musculature. The acute response to stretching has been attributed to two factors: neurophysiologic factors, due to a muscular resistance that is secondary to the reflexive activity and mechanic factor which is associated to the muscular spindle activation. Another factor would be the decrease in viscoelasticity resulting from a stretching tolerance increase. The stretching chronic effect is related to the serial gain of both, sarcomerers and muscular length, enabling muscle to adapt to a new and longer length, as well as increasing the individual’s ROM. The objective of the present study was to analyze the influence of diathermy by applying short waves and cryotherapy on hamstrings muscles flexibility and to observe its acute and chronic effects. Thirty volunteers insufficiently active, male, with hamstrings muscle shortening, aging between 18 and 25 years were selected. The individuals were randomly divided into three groups (n=10): Group 1) passive stretching preceded by cryotherapy; Group 2) passive stretching preceded by continuous short wave heating Group 3) passive stretching only (control). This procedure was made five days a week for two weeks, which totaled 10 sessions. All the volunteers were measured in relation to their maximum hip flexure before and after each stretching session, in order to evaluate the acute effects of the intervention, while the measurements made on the first and last day of the experiment, were used to evaluate the chronic effects. All three groups showed an increase on their hip flexion ROM for both, acute and chronic effects. G1 and G2 had a significant ROM increase in relation to G3, being the response of G1 the most significant of the three. Thus it can be concluded that both acute and chronic stretching effects can be enhanced by the application of cryotherapy before and after passive stretching.